Effects of luseogliflozin on estimated plasma volume in patients with heart failure with preserved ejection fraction. (3rd November 2021) - Nakashima, Mitsutaka; Miyoshi, Toru; Ejiri, Kentaro; Kihara, Hajime; Hata, Yoshiki; Nagano, Toshihiko; Takaishi, Atsushi; Toda, Hironobu; Nanba, Seiji; Nakamura, Yoichi; Akagi, Satoshi; Sakuragi, Satoru; et al.
Abstract: Aims: Sodium glucose co‐transporter 2 inhibitors have diuretic effects in both patients with glycosuria and with natriuresis. We sought to assess the effect of luseogliflozin on estimated plasma volume (ePV) in patients with type 2 diabetes and heart failure with preserved ejection fraction (HFpEF). Methods and results: This study was a post‐hoc analysis of the MUSCAT‐HF trial (UMIN000018395), a multicentre, prospective, open‐label, randomized controlled trial that assessed the effect of 12 weeks of luseogliflozin (2.5 mg, once daily, n  = 83) as compared with voglibose (0.2 mg, three times daily, n  = 82) on the reduction in brain natriuretic peptide (BNP) in patients with type 2 diabetes and HFpEF. The analysis compared the change in ePV calculated by the Straus formula from baseline to Weeks 4, 12, and 24, using a mixed‐effects model for repeated measures. We also estimated the association between changes in ePV and changes in other clinical parameters, including BNP levels. Luseogliflozin significantly reduced ePV as compared to voglibose at Week 4 {adjusted mean group‐difference −6.43% [95% confidence interval (CI): −9.11 to −3.74]}, at Week 12 [−8.73% (95%CI: −11.40 to −6.05)], and at Week 24 [−11.02% (95%CI: −13.71 to −8.33)]. The effect of luseogliflozin on these parameters was mostly consistent across various patient clinical characteristics. The change in ePV at Week 12 was significantly associated with log‐transformed BNP ( r  = 0.197, P  = 0.015) and left atrial volume index ( r  = 0.283, P  = 0.019). Conclusions: Luseogliflozin significantly reduced ePV in patients with type 2 diabetes and HFpEF, as compared with voglibose. The reduction of intravascular volume by luseogliflozin may provide clinical benefits to patients with type 2 diabetes and HFpEF.